Effect of aspect on soil temperature and growth of Hevea on hills of North East India - Saseendran S A; Mandal D; Potty S N; Sethuraj M R; Sinha R R; Vijayakumar K R (Indian Journal of Natural Rubber Research, 1993)
Effect of aspect on soil temperature and growth of Hevea trees on a gently undulating terrain (slope about 25 degree C) of North East India was studied. Soil temperatures under Hevea at depths 5, 10 and 20 cem on a south facing slope was found to bte significantly higher than that on a north facing slope during the winter months. The difference in temperature was not found to exist during the summer months. Slope orientations were also found to influence the growth of Hevea trees. Girth of the trees on the south facing slope was observed to be significantly higher than on the north facing slope. At the end of 6th year of planting, a mean difference of 9 cm in girth of the trees on these aspects was observed.
Keywords: Aspect; Aspect; Hevea brasiliensis; Hevea brasiliensis; North East India; North East India; Soil temperature; Soil temperature